Analysis of active compounds in kawista leaf (Limonia acidissima L.) fraction and its antioxidant activity using DPPH method - Azizah, Tri Nur; Harmastuti, Nuraini; Wijayanti, Tri (Universitas Islam Indonesia, 2024)
Background: Kawista (Limonia acidissima L.) is a plant that has been studied for its potential as a natural antioxidant. Research regarding kawista leaves has not been carried out to a more specific stage, so further fraction separation is carried out to determine compounds that have potential as antioxidant agents.Objective: This study aimed to determine the antioxidant activity of kawista leaf fractions using the DPPH method and to determine the active compounds in the highest antioxidant agents of kawista leaf fracton.Method: Kawista leaves were extracted by re-maceration using methanol, which was then purified by the liquid-liquid extraction method with the solvents n-hexane, ethyl acetate, and water. Phytochemical studies were carried out on the fractions using TLC on flavonoids, steroids, tannins, saponins, and alkaloids. The fraction was separated by the vacuum liquid chromatography method with 11 eluents, which were then tested for antioxidants and characterization of the most active compounds in the kawista leaf fraction. Then the highest results as antioxidant agents from the fraction were characterized for their active compounds using a spectrophotometer and FTIR.Results: The results of the study showed that the most active purified extract in antioxidant activity was ethyl acetate, which indicates strong antioxidant activity. The combined fraction 2 (F2) indicates flavonoid compounds that played an active role as very strong antioxidants with an AAI value of 3.3808, which is not significantly different from the vitamin C as standard. Flavonoid compounds that have been characterized using a spectrophotometer interpret the wavelength shift data that possible F2 belongs to the flavanon group.Conclusion: Active compounds from kawista leaf fraction (F2) have the highest antioxidant agent, with the possibility that flavonoid compounds from F2 belong to the flavanon group.